Analisis Komunikasi Organisasi pada Pengkaderan Pimpinan Cabang Ikatan Mahasiswa Muhammadiyah Palangka Raya: Analysis of Organizational Communication in the Leadership Training of the Palangka Raya Branch of the Muhammadiyah Students Association - Firdaus, Aldi; Swarnawati, Aminah (Anterior Jurnal, 2025)
The Palangka Raya Muhammadiyah Student Association Branch Leadership experienced a gap in management since the 2023-2024 academic year. During the transition to the 2024-2025 period, the journey experienced changes. The prominent changes seen in the quantity and quality of members created a gap in running the organization, so that it became passive in the movement, resulting in a decrease in interest in cadre formation to become leaders who will manage in the 2024-2025 period. The study aims to analyze organizational communication in cadre formation between administrators and PC IMM Palangka Raya members. This study uses a qualitative approach with a descriptive type. Data collection techniques were carried out through interviews and documentation, with data validation techniques using triangulation. The informants were selected based on the author's view that the informant had knowledge and information regarding the problem the author was researching. The study results indicate that communication in the cadre formation in PC IMM Palangka Raya is internal and external. Where this form of internal communication provides freedom to convey information both from leaders to administrators, administrators to leaders, members to administrators, and members to leaders, while external communication is centered on PC IMM Palangka Raya as a forum for aspirations to convey between other commissariats according to the scope of the organization's duties. The cadre formation system in PC IMM Palangka Raya applies formal and informal cadre formation. However, the process by their administrators and representatives from each commissariat differs in developing members according to the organization's focus areas.